Analysis of the Pedagogical Competence of Indonesian Language Lecturers: A Study of Learning Strategies and Quality - Tridays Repelita; Sholeh Hidayat; Nurul Anriani; Depi Prihamdani; Yogi Nugraha (Newinera Publisher, 2025)
Higher education plays a strategic role in producing qualified professional educators, one of which is through strengthening the pedagogical competence of lecturers. This competence is a key factor in determining the quality of learning in higher education. In the Indonesian Language Study Program at Buana Perjuangan University Karawang, lecturers' pedagogical competencies play an important role in the application of learning strategies and the achievement of student learning outcomes. However, research that specifically examines the relationship between lecturers' pedagogical competencies, learning strategies, and learning quality is still limited. This study aims to evaluate the pedagogical competencies of Indonesian language lecturers based on two main focuses, namely the learning strategies applied and the quality of learning produced. The research uses a qualitative descriptive approach with an evaluative study design. The research subjects were lecturers teaching Indonesian language courses, while the objects included aspects of learning planning, implementation, and evaluation. Data were collected through interviews, observations, documentation, and student questionnaires. Data analysis was conducted using the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawing, and was validated using source and technique triangulation. The results of the study indicate that the pedagogical competence of lecturers is in the good category, with the highest achievement in the aspects of learning evaluation (88%) and understanding student characteristics (85%). However, the aspects of technology utilization and student potential development still need to be improved.